Beneficial Metabolic Effects of Praliciguat, a Soluble Guanylate Cyclase Stimulator, in a Mouse Diet-Induced Obesity Model - Schwartzkopf, Chad D.; Hadcock, John R.; Liu, Guang; Germano, Peter; Roux, Julien; Shea, Courtney M.; Buys, Emmanuel S.; Jones, Juli E. (Frontiers in Pharmacology, 2022)
Praliciguat is a soluble guanylate cyclase stimulator that elicits hemodynamic, anti-inflammatory, and antifibrotic effects in preclinical models of metabolic dysfunction. We assessed the metabolic effects of praliciguat in a mouse diet-induced obesity (DIO) model housed at thermoneutrality. At 6 weeks old, male C57BL/6N mice were either maintained on low-fat diet (LFD, lean mice) or placed on 60% high-fat diet (HFD, DIO mice). At 14 weeks old, the DIO mice were either maintained on HFD or switched to HFD with praliciguat (6 mg/kg). Day 28 samples were collected for biomarker analysis. In a second study under the same paradigm, indirect calorimetry was performed on days 8, 9, 20, 21, 32, and 33 and an oral lipid tolerance test (LTT) on day 38. Mice treated 28 days with praliciguat had lower levels of fasting plasma insulin, C-peptide, triglycerides, and HOMA-IR than DIO controls. In addition, energy expenditure was higher in praliciguat-treated than in DIO control mice on days 9, 20, 32 and 33; and day-38 triglycerides were lower. HFD-induced increases in gene expression of liver TNF ɑ, lipoprotein lipase (Lpl), and patatin-like phospholipase domain-containing protein 3 (Pnpla3) in control DIO mice were attenuated in praliciguat-treated DIO mice. The positive metabolic effects observed in praliciguat-treated mice were associated with the restoration of liver PI3K (pAKT-Thr308) signaling, but not MAPK (pERK). In conclusion, praliciguat-treated DIO mice had increased energy utilization, improved insulin sensitivity, and lower plasma triglycerides. These results illustrate metabolic effects associated with praliciguat treatment in DIO mice.